Study on the Reuse of a Waste Landfill from Physical and Chemical Properties and Biodegradability of Landfill Waste Assessment - Chung, Jindo; Park, Kiryul (Asian Journal of Chemistry, 2013)
This paper assessed the physico-chemical characteristics and biodegradability of wastes buried on Sindong landfill, Asan City, Chungcheongnam-dowhose service life was about to end and conducted a basic study to reuse a landfill. There were three sampling spots on Sindong landfill, Asan city, Chooncheongnam-do. The spots were divided into three areas by terms of years for reclamation. Samples were collected both from upper and lower areas and their physicochemical characteristics were explored while an analysis of biodegradability assessment (AT4, BMP) was conducted. Based on the results, the contents of combustibles were very high. This result enables us to assume that the contents of vinyl and plastic materials of low decomposition speeds were high in the wastes previously introduced on Sindong landfill. Based on the results from analyses of the three components covering water, combustibles and lime, the highest level of water content was 43.06 % in the lower area of W-1 while its lowest level was 25.38 % in the upper area of W-2. Water contents were higher in the lower areas where samples were collected. It can be said that based on the characteristics of a sanitary landfill, there is an impact of shield skirts as leachate treatment facilities in the lower area of a landfill. Anaerobic (BMP TEST) biodegradability as one of the ways to assess biodegradability of wastes was around 20 %, which is lower than that of general wastes amounting to 52.8-78.3 %. Based on the results from aerotropic (AT4) assessment, the oxygen consumption in buried wastes was 5.44-19.12 mg O2/g dry matter. On all sample collection sites, the results were 25 mg O2/g dry matter or below, which is the standards for advance stabilization. The results from our analyses provided basic materials for the reuse of Sindong landfill. The basic materials will be able to contribute to finding ways to use and maintain a landfill with their service term ending soon and design processes for the reuse of Sindong landfill.